Interstitial lung macrophages interact with dendritic cells to present antigenic peptides derived from particulate antigens to T cells. - Gong, J L (1994)
When the protective structural and functional barriers of the lung are breached, immune responses must be generated in order to contain invading micro-organisms. This requires the presence of accessory cells capable of phagocytosing and presenting immunogenic peptides to either naive or sensitized T cells. In contrast to dendritic cells (DC) present in the airway epithelium, those within the lung parenchyma do not readily engulf particulates and, therefore, other mechanisms must account for their apparent ability to present immunogenic peptides derived from micro-organisms. The purpose of the present study was to determine the extent to which interstitial macrophages (IM) interact with lung DC to process and present antigenic peptides, derived from particulate, heat-killed Listeria monocytogenes (HKL), to HKL-immune T cells. Results show that highly purified Ia- lung IM avidly phagocytose fluorescent-labelled HKL, but they do not present antigen to primed T cells. Their ability to present antigen is only modestly increased following interferon-gamma (IFN-gamma) stimulation. Conversely, mature DC isolated from the lung interstitium do not phagocytose fluorescent-labelled HKL. In antigen presentation assays, however, addition of 10% (2.5 x 10(3)/ml) Ia- IM to DC and HKL results in a two- to threefold increase in antigen presentation by DC to HKL-immune T cells. Conditioned medium (CM), generated by 2.5 x 10(4)/ml IM induced to phagocytose HKL, when administered to DC and HKL-sensitized T cells without added intact HKL, resulted in brisk mitogenesis, a response that did not occur in T cells sensitized to an irrelevant antigen. Conditioned medium derived from larger numbers of IM was inhibitory. When IM phagocytosed inert polystyrene beads, the resulting CM induced modest T-cell mitogenesis, suggesting that small amounts of cytokines were released. The results indicate that in small numbers, IM augment DC function, in part, by the release of antigenic peptides which are then presented by DC to T cells. When present in numbers greater than 50% of DC, however, they inhibit DC function, probably due to the release of soluble inhibitors.